Savings and shock-coping behavior in South Africa's metropolitan townships - Santamicone, Maurizio (Research of GSB, 2018)
In this paper we study savings behavior in South African Metropolitan Townships and households' ability to manage "shocks" ex-post to their occurrence. In particular we want to determine if the availability of instruments like mobile-money solutions, that allow households to save anywhere , anytime, next to community savings schemes like stokvels and more traditional ones like funeral plans, insurance and bank accounts affects the savings behavior to the extent of improving households' shock-coping strategies. We investigated how variables like education level achieved, employment status and approach to life of the respondents influence their behavior. Poor people periodically face a variety of "shocks", events that can be overwhelming, like ill-health or death of a family member (sometimes the breadwinner), or natural disasters causing loss of home or crop. By providing them with means to save anywhere, anytime they have a chance to mitigate shocks by saving over time, enabling them increase their productivity, maintain their expenditure on nutrition and education during hard times and preventing them from falling back into poverty. While many scholars argue that poor people do have surplus money to save, and the data from this research confirms this statement, traditional financial institutions, especially large commercial banks, find it hard to reach these customers as it is too costly to establish branches in remote areas and they do not have business models to deal with a large number of customers that require low savings and small transactions. Instead mobile operators have experience and technology in place in handling low-value, high-volume transactions and can therefore run the payment and account management platforms instead (or on behalf of) banks. We interviewed 528 households in the Metropolitan Township of Khayelitsha, Cape Town and found statistical evidence that employment status, education level and approach to life affect savings behavior and the adoption of an "optimal" vs. "sub-optimal" strategy when facing unexpected events or shocks. Usage of mobile-money products is low as only 15% of the sample declared to use any of them: this can be partially explained by the fact that bank penetration in the Metropolitan Townships is surprisingly high, with 80% of the population formally banked as confirmed by other studies. We did not find enough statistical evidence that savings through mobile-money instruments improves shock-coping behavior although all the respondents who use some mobile-money product indicated that they perceive an improvement in their ability to deal with unexpected events. We found statistical evidence that education level, employment status and approach to life affects savings behavior and the financial situation of the household. Correlation tests showed statistically significant relationships between better strategies and employment status or education level. Respondents who save using use methods that do not allow immediate withdrawals of the funds like stokvels or funeral plans adopt better strategies than those who rely only on bank accounts.